The Future of Voluntary Hospital Contributory Schemes - The point of view of the wage earning community / by H. H. Elvin - Elvin, Herbert Henry
1938-12-14 1938 1930s 7 pages Voluntary Hospital Contributory Schemes, WAGE EARNING COMMUNITY'S VIEW 2. We are all aware that in our lifetime a great improvement has taken place in the atmosphere, attention given to patients, and the amenities of our Hospitals. In some there is still room for improvement, Because of what I have said, workers have more than an academic interest in Hospitals. Their life is profoundly affected by them. Whilst conscious and glad of the improvements made, they are far from satisfied with the position. They cannot understand, and will not accept the inequality which exists in the treatment of themselves and their loved ones as compared with the assistance which others receive. If it be true, as one has said, that all are born healthy, then the concomitant should be that all should receive equal opportunity to maintain health at its highest pitch. That demand is made in many quarters. I have referred to changes which have taken place. I can remember the time when members of the working classes were generally dependent upon Hospital "letters" to secure treatment in our Hospitals. This was a most degrading form of charity. "Letters" are still in existence, but in so far as the Hospitals Service Scheme has tended to abolish these and to enable the workers to be more independent and maintain their dignity, this is all to the good. Perhaps it is important at this stage, and in view of what I have to say later, that whilst I welcome this Scheme for the reasons given, it must not be assumed that I am heartily in favour of the Voluntary Hospitals system. I consider that the question of national health and fitness is one primarily of Government responsibility on behalf of the country as a whole. Because of this I am a critic of the Government's National Fitness scheme. The idea is right, but the methods adopted are entirely wrong. In the first instance, through faulty terms of reference workers are barred from getting financial assistance from the nationally contributed fund, and it is a case all over again of "for whosoever hath, to him shall be given, and he shall more abundance; but whosoever hath not, from him shall be taken away, even that he hath". And secondly, the Government ignores the basis of national fitness, viz., material sustenance and frequent medical examination. Again, until national health becomes the affair of a special State Department, co-ordinated with a Ministry of Leisure, and until it is realised that from the State point of view if the organisation of Air Raid Precautions requires a whole Ministry the organisation of Disease Raid Preventives is much more imperative, I am glad that there exists the British Hospitals Contributory Schemes Association. For the reasons already mentioned, The British Trade Union Movement takes a keen interest in work of this kind. As is known it has its own Social Insurance Committee and Medical Officer. 292/842/2/220